2010
DOI: 10.3346/jkms.2010.25.5.785
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Rhabdoid Tumor of the Kidney Combined with Multicystic Dysplasia in a 5-year-old Child

Abstract: Multicystic dysplastic kidney (MCDK) is a relatively common developmental anomaly in infants and children and has a good prognosis. In contrast, a malignant rhabdoid tumor of the kidney (MRTK) is one of the most lethal neoplasms of early life. However, the presentation of such a lethal tumor combined with multicystic dysplasia has not been reported to date. In this report, we describe a case of MRTK in a 5-yr-old girl who also had multicystic dysplasia. She was previously diagnosed with MCDK at birth due to a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…There is no evidence for an increased risk of malignancy in MCDK in children and young adults; therefore, monitoring solely to exclude malignancy is unnecessary.-Despite case reports of various malignancies coinciding with MCDK (33)(34)(35)(36), numerous cohort studies with follow-up during childhood have not shown an increased risk of malignancy (Table E3 [online]).…”
Section: Simple Cystmentioning
confidence: 99%
“…There is no evidence for an increased risk of malignancy in MCDK in children and young adults; therefore, monitoring solely to exclude malignancy is unnecessary.-Despite case reports of various malignancies coinciding with MCDK (33)(34)(35)(36), numerous cohort studies with follow-up during childhood have not shown an increased risk of malignancy (Table E3 [online]).…”
Section: Simple Cystmentioning
confidence: 99%